The Integrated Impact of Metabolic, Dietary, Environmental, and Psychological Factors on Psoriasis – An Interdisciplinary Perspective on an Inflammatory Skin Disease - Edyta Witkowska; Marcin Ciechański; Klaudia Wilk; Szymon Cholewiński; Bernadetta Wilk; Piotr Stachura; Piotr Rejman; Katarzyna Pszczoła; Katarzyna Jurkiewicz; Aleksandra Kasprzyk (Quality in Sport, 2025)
Introduction, purpose: Psoriasis is a chronic, non-infectious skin disease. It is estimated that approximately 2–3% of the global population is affected by this condition. Its prevalence varies geographically — higher rates are observed in Europe and North America, while lower rates are noted in Asia and Africa. The development of psoriasis is influenced by genetic predisposition, immune system dysfunction, as well as environmental factors. Psoriasis is not only a dermatological issue characterized by excessive keratinocyte proliferation, but also a systemic inflammatory disease that impacts the patient’s psycho-emotional well-being and carries an increased risk of numerous complications.